Impact of Remittances on Financial Development in Vietnam - Pham, Thi Hoanh Oanh (University of Economics Ho Chi Minh City, 2023)
This study focuses on the impact of remittances on Vietnam’s financial development. The results drawn from its quantitative approach demonstrate that although remittance flows to the country may lead to increase in bank deposits, such increase is not high. On the other hand, reduction in credit demands may be subject to remittance flows, per the financial development based on a few credit growth indicators. In other words, effects of remittance flows, as indicated by VAR model, are not noticeable despite their positive impact, as in examples of increased deposits and remittance payment services on their current growth. Based on these findings, the study suggests several implications that improve the positivity of impact on the financial development.